Best trigonometric and bilinear approximations for the classes of $(ψ, β)$ -differentiable periodic functions - Shkapa, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish the exact-order estimates for the best $m$-term trigonometric approximations of the classes $L^{ψ}_{β, 1}$ in the space$L_q,\; 2 < q < ∞$. We also determine the exact orders of the best bilinear approximations for the classes of functions of twovariables generated by functions of a single variable from the class$L^{ψ}_{β, p}$ by the shifts of the argument in the space $L_{q_1,q_2},\; 1 ≤ q_1,\; q_2 ≤ ∞$.